Analysis of the Influence of Revenue Sharing Funds, General Allocation Funds, and Special Allocation Funds on Economic Growth in Java - Alexzander, Afrixson Leonardo; Wahed, Mohammad (Indonesian Journal Publisher, 2026)
This study aims to analyze the influence of Revenue Sharing Funds, General Allocation Funds, and Special Allocation Funds on economic growth in Java Island in the period 2015–2024. The independent variables in this study include Revenue Sharing Funds (DBH), General Allocation Funds (DAU), and Special Allocation Funds (DAK), while the dependent variable is regional economic growth. This study uses a quantitative descriptive method and data analysis is carried out using panel data regression. The results of the study indicate that Revenue Sharing Funds (DBH) and General Allocation Funds (DAU) have a positive and significant effect on economic growth in Java Island, which means that increasing DBH and DAU revenues can encourage economic activities to increase regional development capacity. Conversely, the Special Allocation Fund (DAK) has a negative but significant effect on economic growth, which indicates inefficiency in the allocation and use of these funds. Overall, the results of this study confirm that the management of balancing funds is highly dependent on the ability of local governments to manage financial resources efficiently, transparently, and accountably in order to encourage sustainable economic growth at the regional level.